2017
DOI: 10.1177/1464420717702176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frequency on hysteretic heating and fatigue life of unreinforced injection molded polyamide 66 spur gears

Abstract: Gears are subjected to different rotational speeds/frequencies during their service life. The effect of the rotational speed on the performance of a metal gear is insignificant; however, it affects the thickness of the lubricant film. Polymer gears generate hysteretic self-heating because of the viscoelastic behavior of the material, thereby limiting their performance and usage in applications. The injection molded polyamide 66 spur gears were loaded by ground steel gear at different torques and frequencies us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Generally, higher cycling frequencies are not recommended for polymer testing, as the internal heat generation weakens the strength of the material. 18,20 However, for tests entailing considerably longer durations, accelerated testing is warranted. As bending fatigue tests are typically time-consuming, a higher cycling frequency was deemed appropriate.…”
Section: Test Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, higher cycling frequencies are not recommended for polymer testing, as the internal heat generation weakens the strength of the material. 18,20 However, for tests entailing considerably longer durations, accelerated testing is warranted. As bending fatigue tests are typically time-consuming, a higher cycling frequency was deemed appropriate.…”
Section: Test Methodologymentioning
confidence: 99%
“…A concise account of the test rig is provided in this section, as the test rig components are comprehensively described elsewhere. 17,18 The system was powered by a servo motor (BALDOR, BDM -100C -3250), which was regulated by a servo drive (Motiflex). The loading and control systems are connected to the human machine interface, which allowed the user to set the torque and cycling frequency.…”
Section: Description Of Bending Fatigue Test Rigmentioning
confidence: 99%
“…35 Polymer gears undergo hysteretic heating during bending fatigue tests. 28 The heat generated during the bending fatigue test and its influence on the fatigue performance was not quantified in this study. The operating temperature of polymer gears under service condition is substantially higher than the temperature rise caused by hysteretic heating during bending fatigue tests.…”
Section: Bending Fatigue Life Of Symmetric and Asymmetric Gearsmentioning
confidence: 97%
“…A detailed description of the test rig has been given elsewhere. 28
Figure 2.(a) Bending fatigue test rig; (b) human–machine interface device; (c) schematic of the test rig.
…”
Section: Test Rig Descriptionmentioning
confidence: 99%
“…Kodeeswaran et al [9] attempted to evaluate the performance of unidirectional and bi-directional load polyamide gear. Results concluded that thermomechanical and root crack were detected in the case of bi-directional loading.…”
Section: Introductionmentioning
confidence: 99%